2023
DOI: 10.1088/2053-1591/acf43f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically modulating the mid-infrared localized surface plasmon resonance of Al-doped ZnO nanocrystals

Yan Jia,
Dongqing Liu,
Xinfei Wang
et al.

Abstract: The localized surface plasmon resonance (LSPR) regulation of semiconductor oxide nanocrystals (NCs) in the near-infrared region (0.8–2.5 μm) of the solar spectrum has attracted much attention for its potential in applications such as electrochromism and sensing. However, the LSPR modulation properties of doped semiconductor oxide NCs in the mid-infrared region (2.5–25 μm) have rarely been reported. Here, we synthesized aluminum-doped zinc oxide (AZO) NCs with various nominal Al doping contents (1–20at%). The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Rensberg et al [39] demonstrated that the wavelength at which the permittivity of AZO is equal to zero can be arbitrarily controlled from 3.7 to 9.2 mm by varying the freecarrier concentrations. Yan et al [40] synthesized AZO NPs with various nominal Al doping contents. The LSPR absorption peaks of these films were regulated between 3.8 and 6.57 mm depending on the doping content.…”
Section: Introductionmentioning
confidence: 99%
“…Rensberg et al [39] demonstrated that the wavelength at which the permittivity of AZO is equal to zero can be arbitrarily controlled from 3.7 to 9.2 mm by varying the freecarrier concentrations. Yan et al [40] synthesized AZO NPs with various nominal Al doping contents. The LSPR absorption peaks of these films were regulated between 3.8 and 6.57 mm depending on the doping content.…”
Section: Introductionmentioning
confidence: 99%